Does Institutional Pressures Leads to Better Green Supply Chain and Organizational Performance in Indonesian Manufacturing Sector: Role of Senior Management and Social Capital - Taufan Maulamin; Paisal Halim; Syamsiah Badruddin; Zulkarnain Hamson; Imran Ismail (International Journal of Supply Chain Management, 2020)
The research examines the influence of three organizational pressures (such as, government, customer and rivals) on performance associated with environment and operations. These three organizational forces are analyzed by adopting green supply chain management (GSCM), considering the senior management and examining social capital in the supply chain between buyers and sellers. Information was obtained by an email questionnaire from buying companies in Indonesian manufacturing sector. The analysis was based on structural equation modeling (SEM) and applied on 250 available responses from Indonesian manufacturing sector to evaluate our hypotheses. Our findings demonstrated that almost all hypotheses are accepted. Our research expands the GSCM literature by incorporating significant and latest concepts into the GSCM theory, and at the same time offering implications for policy making through empirical evidence.